Malacoplakia or prostate cancer? Similarities and differences - Agostinho, Aparecido Donizeti [UNESP]; Corrêa, Luiz Antonio [UNESP]; Amaro, João Luiz [UNESP]; Bacchi, C. E.; de Camargo, JLV (Karger, 1998)
Malacoplakia is a granulomatous inflammatory disorder clinically and ultrasonographically very similar to prostatic adenocarcinoma. Symptoms and physical findings are similar to prostatism and in half of the patients the differential diagnosis includes malignancy, mainly because of the presence of a hard nodule on digital rectal examination. Additionally, cases of malacoplakia can show hypoechoic nodes on transrectal ultrasound mimicking adenocarcinoma. We report a case of malacoplakia of the prostate with emphasis on its similarities and differences with prostate adenocarcinoma.
Keywords: malacoplakia; prostate; cancer, prostate; adenocarcinoma, prostate